“Computers can land people on Mars, why can’t they get them to work in a hospital?” - Jones, M. R. (Methods of Information in Medicine, 2003)
Objectives: This paper aims to describe and interpret the implementation of a hospital information system in a large UK hospital.Methods: The paper is based on a longitudinal case study over a three-year period in which a cross section of hospital staff involved with the information system were interviewed.Results and Conclusions: Ambitious government targets for the use of Information Technology in the UK National Health Service sit alongside a history of notable project failures. The decision by a UK hospital to install an advanced, integrated electronic patient record system therefore faced conflicting demands and expectations. This paper suggests that its simple categorisation as either a success or failure is problematic. Rather, the differing viewpoints that lead some clinicians to express “disappointment” with its performance, while others described its features as “tremendous” and managers suggested that the system had become “taken for granted” are explored. A number of broader phenomena relating to the organisational processes surrounding information systems implementation are also identified.
Keywords: Hospital information systems; electronic patient record system; implementation; implementation failure; National Health Service (NHS) ICT strategy